Sharing Knowledge Dan Studi Tiru Budi Daya Jamur Untuk Peningkatan Pendapatan - Arifin, Zainul; Bunyamin, Bunyamin; Munfaqiroh, Siti; Sa’adah, Lailatus; Erawati, Sherly Hesti; Sugiono, Djoko (STIE Malangkucecwara, 2023)
The service activities at